The Role of Religious Education Teachers in the Character Formation of Pancasila Student Profile Dimensions of Faith - Rizki Septa Hardhita Hardhita (Lembaga Pendidikan Islam Ma'aarif NU Kabupaten Magetan, 2022)
In an era of increasingly rapid technological development, today many people are addicted to Gadgets. It can be seen from the number of users of gadgets (smartphones) globally increasing from year to year. The high use of excessive or inappropriate gadgets has an influence on the personality and character of the community. It can be seen from the many cases that reflect the bad character of Indonesian society, such as corruption, cyberbullying, brawls between lessons, and other cases (Bura & Puspito, 2011). The purpose of this study was to determine the role of religious teachers in the character formation of pancasila student profile dimensions of faith, fear of God, and noble character in the Laboratory Primary School of UM Blitar. This study used a qualitative descriptive research design with a case study approach. The data collection techniques used in this study were interviews and documentation studies. This research was conducted at Laboratory Primary School UM Blitar, with the religious teacher as the key informant. This study shows that the role of religious teachers in the formation of student character is needed by students because the presence of religious education teachers who act as parents of students would have a very large role in order to educate students to be faith, Fear of God, and Noble Character. The role of a religious teacher in the formation of student character includes empowerment, exemplary, intervention, integration, and screening. Strategies undertaken by religious teachers in the formation of student character include 3s habituation (smile, say hello, greetings), habituation to pray based on their religion, prayer reading, discipline habituation, and honest habituation.